New oral anticoagulants in patients undergoing atrial flutter radiofrequency catheter ablation: an observational study. (November 2014) - Amara, Walid; Fromentin, Stéphane; Dompnier, Antoine; Nguyen, Cédric; Allouche, Emna; Taieb, Jérôme; Georger, Frédéric; Saoudi, Nadir
ABSTRACT : Aim: Atrial flutter (AFL) ablation requires optimal periprocedural anticoagulation in order to minimize thromboembolic events/bleeding risk. This study describes the characteristics of patients receiving new oral anticoagulants before AFL ablation and assesses complications.Methods: This multicenter, retrospective study reports ischemic and hemorrhagic predischarge, postprocedural complications.Results: We evaluated 60 patients (62.3% male; mean age: 69.2 ± 9.7 years; CHA2 DS2 -VASc score: 2.44 ± 1.46, HAS-BLED score: 1.14 ± 0.7). Twenty-one (35.0%) and 23 patients (38.3%) received twice-daily dabigatran 110 or 150 mg; 16 patients (26.6%) received once-daily rivaroxaban (15 mg [n = 5] or 20 mg [n = 11]). Four cases of postprocedural minor bleeding were reported.Conclusion: This is the first study assessing new oral anticoagulants for periprocedural anticoagulation, specifically in patients undergoing AFL ablation. No major bleeding was reported. Further prospective investigation is warranted.